A new type of truss joint for prevention of progressive collapse. (15th July 2018) - Yan, Shen; Zhao, Xianzhong; Chen, Yiyi; Xu, Zhenyu; Lu, Yong
Highlights: PS joints maximize the function of catenary action upon a sudden member removal. Design method for sliding resistances and components of PS joints was put forward. A planar truss was tested to verify the effectiveness of the PS joints. FE analyses show PS joints work properly under all progressive collapse scenarios. Abstract: This paper presents a study on a new type of truss joint (Pinned-Slidable or PS joint) that is designed to maximize the function of catenary action upon a sudden member removal. The basic idea for a PS joint is such that it is fixed on the bottom chord without sliding under the design load, but can slide along the bottom chord to help distribute the unbalanced tensile forces that the catenary action generates on different bottom chord members. The sliding resistance of this joint is provided by the friction generated by the preloaded bolts and the shear resistance of a locking rod, which can be designed according to the proposed design schemes. A Warren truss with PS joints as the bottom joints (Truss-PSJ) has been designed and tested under a scenario of a sudden removal of one of its diagonal members, and the response of the structure is compared with that of an identical truss model except for its non-slidable joints (truss-PJ). Results show that significant catenary action develops in the bottom chord of the remaining structure in the process of establishing a new equilibrium state after the member removal, and the catenary action tends to generate much larger tensile forces in the bottom chord members in the mid-span than in the neighboring bottom chord members, leading to the sliding of a PS joint. By comparing the test results of truss-PSJ with those of its counterpart truss-PJ, the benefits of the PS joints have been clearly demonstrated. The sliding of the PS joint not only releases the excessive unbalanced forces between neighboring members and thus enables a fuller development of the catenary action, but also facilitates the adaptation of the remaining structure towards a new balanced state with a near-optimal deformation shape. A finite element analysis has also been conducted to confirm the above experimental observations, and to demonstrate the performance of PS joints under other progressive collapse scenarios. Furthermore, a method for determining the sliding resistance of PS joints is also proposed.